A Meta-Analysis of Presuppositions by Native and Second Language Speakers - Yuqi Chen (Ilmu Inovasi Nusantara, 2026)
In recent years, research on second language acquisition has increasingly focused on complex linguistic phenomena that remain difficult for second language learners to fully master, even at advanced proficiency levels. One such phenomenon involves the comprehension and use of pragmatic presuppositions, which require integrating semantic meaning with pragmatic context. Many second language learners experience persistent difficulties in processing linguistic features located at the interface between linguistic domains, particularly the semantic–pragmatic interface. The Semantic–Pragmatic Interface Hypothesis proposes that language phenomena situated at external interfaces are more difficult to acquire than those at internal interfaces. Therefore, this study aims to examine the comprehension and acquisition of pragmatic presuppositions among native and non-native speakers. This study employs a meta-analytic approach, systematically reviewing and synthesizing empirical studies on the processing of pragmatic presuppositions in both native and non-native speakers. The analysis compares reported effect sizes across studies to identify general patterns in the ability to generate and adjust presuppositions during language use. The results indicate that both native and non-native speakers can generate and adjust pragmatic presuppositions in communicative contexts. However, the overall effect size observed for non-native speakers is consistently lower than that for native speakers. This finding suggests a measurable difference in mastery levels between the two groups and provides empirical support for the Semantic–Pragmatic Interface Hypothesis, which predicts greater acquisition difficulty for linguistic phenomena located at external interfaces. This study recommends that second language instruction place greater emphasis on linguistic phenomena at the semantic–pragmatic interface. Future research should further explore pedagogical strategies that facilitate learners' acquisition of complex pragmatic features in second-language learning contexts